Amalan Pelaksanaan JIT Dalam Sistem Pengurusan Inventori Bagi Meningkatkan Kecekapan - Buyong, R.; Ahmad, Ahmad Nur Aizat (Research in Management of Technology and Business, 2020)
In this research, Just In Time (JIT) was conducted in the inventory management department. To achieve the objectives of the research, the inventory department needs to reduce waste such as excess finished goods in inventory and lack of raw material inventory. Among the techniques in Lean manufacturing that can be applied to improve the inventory management system is JIT. ABC Analysis and inventory layout are among the methods used to analyze inventory aspect using the concept of JIT. With the concept of JIT, current inventory management can be improved, and a proper inventory management can increase the work effectiveness.